The THE PLASMABLASTIC LYMPHOMA. A STATE-OF-THE-ART REVIEW: PART 2-FOCUS ON THERAPY - Michele Bibas (Mediterranean Journal of Hematology and Infectious Diseases)
The objective of this two-part review is to present a current and comprehensive understanding of the diagnosis and management of plasmablastic lymphoma. The first part, which was published previously, focused on the study of epidemiology, etiology, clinopathological characteristics, differential diagnosis, prognostic variables, and the impact of plasmablastic lymphoma on specific populations. This second part addresses the difficult topic of the treatment of plasmablastic lymphoma, specifically examining both the conventional, consolidated approach and the novel therapeutic strategy.